Reforestyng thoughts or Performagyc actyons and the actor-shaman (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Throughout this article, possible approximations between the performing arts, with an emphasis on the theater-performativity, and the performativity of indigenous shamanisms from the lowlands of South America were approached. In this writing we want to evidence/create certain flows between one and the other, as to say, between the actor-performer and the indigenous shaman. Starting from the analysis of practical practices, as well as the cure(ating) in dialogues with indigenous leaders, shamans, researcher etc. Despite not having a theoretical depth in specific concepts, we call to dance with us seeds of thought such as performative actions, the actor's work with an idea of work on himself, and dreams. Among other images and enchantments, let’s open ourselves to the forest of thinking.
Keywords: Indigenous theater; Performagic actions; Shamanism